The forecast of occurrence of risk of time disability on the basis of a complex estimation of a state of health, working conditions and qualities of a life of workers of shipbuilding - A. V. Ivanchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The aim of the work was to develop a way of the forecast the risk of occurrence in time disability at the workers occupied with shipbuilding. 577 persons, occupied in shipbuilding and ship repair, have taken part in research. Objective data on disease (were estimated according to disease with time disability, morbidity rate and medical surveys), harmful production factors, levels functional intensity of the basic systems of an organism, and also subjective: working conditions and a life, quality of a life. Results: With the help of the factorial analysis it was possible to lower dimension of a correlation matrix with 142 to 34 variables. The close interrelation of the factors describing an estimation of a degree of satisfaction of relations in collective, material compensation of work and pleasure from carried out work with a self-estimation of conformity of work to health, objective parameters of a state of health has been found out. It is established, that up to 35 % of disease it is possible to prevent the competent organization of work within the precincts of the enterprise (normalization of relations in collective, material compensation of work and formation of installations on importance and necessity of carried out work). The most part (53,5 %) at the same time is enough the factors connected to health, poorly gives in to updating as is caused or features of technological process, or features of a way of life working. The problem of the forecast of risk of time disability at the workers occupied in shipbuilding branch has been solved with the help of the consecutive analysis on method of A. Wald in updating E.V Gubler (1990). The received solving rule took into account the characteristics including data on a way of life, character of labour activity, the experience, age, a field, a functional pressure of cardiovascular system. The mistake of the forecast has made less than 10 %. Thus, use of the received mathematical model allows not only it is correct to predict occurrence of time disability at the workers borrowed in ship-building branch, but to define things in common between a state of health, working conditions and quality of a life.